Desain Layout Ruang Kelas dengan Pendekatan Ergonomis Human-Centered Approach - Rohimah, Anni; Saputra, Rahmat; Zuhro, Siti Fatimatul; Atmaja, Sena (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The classroom is a room that functions as a place for theoretical, practical learning activities that do not require special equipment and practice with special tools that are easy to provide. One practice with special tools that is easy to provide is learning Information and Computer Technology (ICT) using a laptop. Not all schools have an ICT practice room. ICT practical activities are carried out in the classroom. Therefore, it is necessary to create guidelines for designing classroom layouts as modifications to classrooms that will be used as ICT practical learning spaces. The method used in designing classroom layouts is an ergonomics approach, namely the Human-Centered Approach. Classroom design using an ergonomics approach is carried out by placing humans at the center of the design or the Human Centered Approach. The design of the classroom layout as an ICT learning space is carried out by adapting to the requirements set out in the Regulations of the Ministry of Education, Culture, Research and Technology which contain classroom requirements and are combined with ergonomic principles. Class layout design begins with creating an initial layout, then a configuration layout and simulating teacher mobility in the configured class layout. The class layout design was made using Microsoft Visio software and the teacher mobility simulation was carried out using Promodel software. From this research, results were obtained in the form of 2 (two) alternative classroom layout designs as ICT learning spaces.